Evaluating the Impact of Collaborative Use of Google Docs and Google Translate on English Learning Performance - Herlinawati Herlinawati; Sri Wahyuni; Anna Merisa (STAI Hubbulwathan Duri, 2025)
The integration of technology in education has become increasingly essential, particularly in language learning. Tools such as Google Docs and Google Translate can enhance collaborative learning by promoting interaction, peer feedback, and improved comprehension. This study investigates the impact of these tools, combined with collaborative learning methods, on students’ English language performance. A quantitative approach using a post-test only design was applied. The sample consisted of 43 tenth-grade students from SMAN Khusus Olahraga Pekanbaru, selected through purposive sampling. Class X Science I (22 students) was designated as Experimental Class 1, and Class X Science II (21 students) as Experimental Class 2. Google Docs facilitated collaborative writing and peer editing, while Google Translate supported vocabulary understanding and sentence construction. A written test was used as the research instrument, and data were analyzed using an independent t-test on the N-Gain Score (%). The independent t-test revealed a significance value of p = 0.685 (p 0.05), indicating no statistically significant difference between the two experimental groups. This suggests that the combined use of collaborative learning and translation tools had a minimal impact on improving students' English performance. The limited effect may be attributed to students’ over-reliance on translation tools, which can hinder language processing and reduce opportunities for critical thinking. Additionally, the short duration of the intervention may have limited the tools' overall effectiveness.